Enzymatic browning and its control in fresh-cut apple - Kumar, Pushpendra; Sethi, Shruti; Nayak, Swarajya Laxmi (Indian Horticulture, 2021)
Enzymatic browning is an economically important physiological problem that impairs the sensory qualities and discourages consumer purchase of fresh-cut apples. Control of browning on fresh-cut apples has been the focus of extensive research and many technologies have been explored with successful results. Research on effective combinations of various chemical compounds above needs to be undertaken since no single treatment can effectively enhance the shelf life of fresh-cut apple wedges while controlling browning and preserving the quality and safety for consumers.